An inductive thematic analysis of male competitive figure skaters' experiences of weight pressure in sport - Voelker, D. K.; Reel, J. J. (Journal of Clinical Sport Psychology, 2018)
The purpose of this qualitative investigation was to examine male competitive figure skaters` experiences of weight pressure in sport. Specifically, male skaters` perceptions of the ideal skating body, sources of weight pressure in elite figure skating, and the perceived role of their sport in shaping body image, athletic performance, eating, and exercise behaviors were explored. Through a social constructivist lens, an inductive thematic analysis was used to examine the contextual influences of the skating environment. Thirteen male figure skaters ages 16-24 (M = 18.53, SD = 3.33) with an average 10.38 years of skating experience (SD = 4.05) were interviewed. Skaters identified the parameters for the ideal body in skating along with specific weight pressures, body image concerns, and weight management strategies. Similar to female skaters, male skaters perceived that body image affected psychological factors that influence sport performance. Sport psychologists and consultants should be attentive to the skating environment and how specific performance and appearance demands may influence an athlete`s mindset.